Coalitions across the Class Divide : Lessons from the Labor, Peace, and Environmental Movements - Rose, Fred (Cornell University Press, 2018)
Too often struggles for jobs and economic justice have been divided from social goals such as peace or protecting the environment. How do we create an economy where both the process and product of work serve life-sustaining goals? Coalitions across the Class Divide argues that the seeds of this new society are being sown by those who learn to bridge working and middle-class movements and cultures. A new generation of activists is seizing a historic opportunity to organize coalitions across the labor, peace, environmental, and other movements that have previously worked in isolation or at odds. Fred Rose brings the challenges and potential of coalition organizing to life through an in-depth look at cases of conflict and cooperation. From the timber wars in the Pacific Northwest to military conversion coalitions emerging with the end of the Cold War, these cases teach practical lessons about the processes and pitfalls of organizing across movements and classes.